(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
An incomplete family is a nuclear family consisting of one parent and children. In Russia, an incomplete family most often consists of a mother and children. Families become incomplete for two reasons: the separation of parents, the death of one of the spouses. Sociologists and psychologists identify the third factor - the birth of a child out of wedlock. In fact, there was no family before birth, so this can hardly be called a reason, rather a condition. But experts put him in second place in terms of exposure (the first is divorce). Among births out of wedlock, births of underage mothers occupy a special place.